Microbial life of the deep saline biosphere - Goraj, Weronika; Stepniewska, Zofia (JOURNAL OF ADVANCES IN BIOLOGY, 2017)
Transfer microbiological studies under the surface of the Earth to exploration of deep intraterrestrial microbial life is important to allows exceeding the current framework of science. Microbial life is determined by physical, geochemical, and biological factors such as the availability of liquid water, energy, nutrients, and trace elements. Additionally, conditions including ambient temperature, pH, salinity, and pressure interact with biological systems to define the space for life. Recent studies have shown the presence and activity of cells in deep marine sediments and in the continental deep biosphere. Characterizing the bacterial community composition and recognition of diversity of microorganisms may play an important role in biogeochemical carbon cycling and potential biotechnological application of these microorganisms.